Research on the distribution law of geohazards along the highways in the Western sichuan plateau gradient zone - Li, Chaofei; Li, Tianbin; Lan, Fuan; Wang, Jianfeng; Ren, Yang; Kou, Xiaomin (Frontiers in Earth Science, 2025)
IntroductionFrequent geohazards along highways in the western Sichuan Plateau gradient zone severely constrain regional development. To clarify the spatial distribution laws and main drivers of highway geohazards is crucial for geohazard prevention and control.MethodsThis study analyzed 2230 geohazard sites within 3 km of 11 highways in the western Sichuan Plateau gradient zone, considering both internal and external geodynamic factors. Additionally, the study further quantified the influence of each conditioning factor on the distribution of geohazards using the Geographical Detector Model (GDM).ResultsThe following conclusions were drawn: (1) The density of geohazard sites along highways in the gradient zone is high, averaging 1.16 sites per kilometer. (2) Highway geohazards exhibit spatial clustering, with higher densities observed in the central part of the gradient zone (e.g., Duwen and Wenma highways) and lower densities at the periphery (e.g., Mianjiu and Majiu highways). (3) The distribution of highway geohazards is significantly influenced by distance to fault zones, vertical deformation gradients, and rainfall, with q values of 0.39, 0.37, and 0.31, respectively. (4) The interaction between any two conditioning factors exhibits a higher q value for geohazard distribution than individual factors.DiscussionDriven by the multi-sphere coupling effects among the tectonic deformation sphere, rock mass relaxation sphere, atmospheric sphere, and engineering disturbance sphere, a geohazard triggering mechanism has been established. This mechanism is primarily controlled by factors such as the distance from the fault zone, vertical deformation gradient, and rainfall, while other factors like elevation and slope serve as secondary controlling factors. The nonlinear synergistic effects between the primary controlling factors and secondary controlling factors significantly amplify the probability of disaster risk. The results quantitatively characterizes the driving factors of geohazards and their nonlinear synergistic effects. It can provide a reference for geological disaster monitoring, preparation of post-disaster emergency measures, and highway planning.